2006
DOI: 10.1007/s10265-006-0283-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the genus Cardiandra based on genetic variation in cpDNA sequences

Abstract: We investigated the phylogenetic relationships within the genus Cardiandra based on plastid DNA sequences. The phylogenetic tree showed that Cardiandra populations from the Ryukyu Islands (Japan) and Taiwan were monophyletic (Ryukyu-Taiwan clade), whereas taxa from China and mainland Japan were sisters to this clade. The divergence time between the Ryukyu-Taiwan clade and the other species was estimated to be 0.082 MYA, i.e., the late Pleistocene. The infrageneric and/or infraspecific differentiation of Cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
0
13
1
1
Order By: Relevance
“…Nevertheless, the traditional view that plant cpDNA changes very slowly in nucleotide sequences is still somewhat valid (Palmer 1990;Provan et al 2001). Such phylogeographic investigations based on genetic variations in cpDNA sequences have already been conducted in angiosperms, including Citrullus and Cardiandra (Dane and Lang 2004;Setoguchi et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, the traditional view that plant cpDNA changes very slowly in nucleotide sequences is still somewhat valid (Palmer 1990;Provan et al 2001). Such phylogeographic investigations based on genetic variations in cpDNA sequences have already been conducted in angiosperms, including Citrullus and Cardiandra (Dane and Lang 2004;Setoguchi et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, in order to understand the evolutionary history of the Japanese flora, it is important to clarify the origins of Japanese endemic plant groups. However, there have been few studies of the phylogenetic divergence patterns of endemic plant groups in the Japanese flora based on objective data, except for studies of plants of the Ryukyu Islands (Hiramatsu et al 2001;Setoguchi 2001;Setoguchi et al 2006) and the Bonin Islands (Ito and Pak 1996;Ito 1998; Japanese species is shown in Fig. 1; P. iwatensis is distributed in northern Honshu, P. nipponica is found on the Sea of Japan side from central to northern Honshu, whereas P. gloriosa occurs on the Pacific Ocean side of central Honshu (mainly in the Kanto district), and P. ochiaiana is distributed only near the summits of the mountains on Yakushima Island, Kyushu.…”
Section: Introductionmentioning
confidence: 99%
“…During the Quaternary period, the island chain from Yaku to Taiwan repeatedly formed landbridges due to sea-level changes induced by climatic oscillations (Kimura, 1996(Kimura, , 2000. Cardiandra plants (Hydrangeaceae) on these islands were shown to have a common ancestor, suggesting that their range expanded along the landbridge, passing from Taiwan to Japan during glacial periods (Setoguchi et al, 2006). To clarify the origin and population history of the OK population of K. septemlobus, further phylogeographic study including samples from mainland China and the Korean Peninsula should be conducted in the future.…”
Section: Strong Isolation Effect Of Straits On Small Insular Populationsmentioning
confidence: 99%